Le cas du metal symphonique, entre dégénérescence d’un art de l’extrême et exaltation du culte de la puissance - Jason Julliot (Criminocorpus)
Born in the late 1990’s, symphonic metal is a genre which divides metal amateurs. This uncomfortable status is due in particular to its composite dimension, which blends an orchestra with the traditional metal formation. After sketching a definition of symphonic metal, this article considers the sound radicality issues in the heavy metal : by reversing the balance in favour of classical instruments and by integrating female singers (potentially lyrical), symphonic metal appears to be a non-violent genre, incompatible with what is the essence of heavy metal music. However, by adding all the power of a symphony orchestra to the metal band, by appropriating the codes of neo-Hollywood symphonism, and by designing oversized gigs, the symphonic metal musician seems to be part of a “cult of power”.